2020
DOI: 10.3390/molecules25163682
|View full text |Cite
|
Sign up to set email alerts
|

Human, Animal and Plant Health Benefits of Glucosinolates and Strategies for Enhanced Bioactivity: A Systematic Review

Abstract: Glucosinolates (GSs) are common anionic plant secondary metabolites in the order Brassicales. Together with glucosinolate hydrolysis products (GSHPs), they have recently gained much attention due to their biological activities and mechanisms of action. We review herein the health benefits of GSs/GSHPs, approaches to improve the plant contents, their bioavailability and bioactivity. In this review, only literature published between 2010 and March 2020 was retrieved from various scientific databases. Findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 194 publications
0
37
0
1
Order By: Relevance
“…When vegetables are thermally processed before consumption, plant myrosinase is inactivated and GLS either partially absorbed in stomach of passed to colon where they are hydrolyzed by the intestinal microbime [ 15 ]. GLSs are reported to have disease prophylactic and therapeutic effects mediated via their anti-inflammatory, antioxidant, chemopreventive, cytotoxic and anti-cancer activities [ 2 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…When vegetables are thermally processed before consumption, plant myrosinase is inactivated and GLS either partially absorbed in stomach of passed to colon where they are hydrolyzed by the intestinal microbime [ 15 ]. GLSs are reported to have disease prophylactic and therapeutic effects mediated via their anti-inflammatory, antioxidant, chemopreventive, cytotoxic and anti-cancer activities [ 2 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…GLS are sulfur-containing secondary metabolites that alongside with their breakdown products exert chemopreventive, anti-tumor and antimicrobial activity [ 45 ]. Current literature has shown that glucomoringin derivatives are able to counteract the inflammatory cascade involved in multiple sclerosis [ 46 ] and exert antibacterial activity [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plants of the Brassicaceae family are characterized by a very effective and specific chemical defense system based on the production of a group of secondary anionic metabolites called glucosinolates (GSLs) [ 26 ]. GSLs consist of a S-ÎČ- d -glucopyrano unit anomerically connected to an O-sulfated (Z)- thiohydroximate function, which represents the invariant backbone of the molecule, which is linked to a variable side chain (or R-Group).…”
Section: Biocompounds In Brassicaceaementioning
confidence: 99%
“…This review aims to provide a comprehensive perspective of the scientific literature focused on the biological role of secondary plant metabolites derived from potato and Brassicaceae wastes such as alkaloids, glycoalkaloids, terpenoids, organic acids, glucosinolates (GSLs), and their hydrolysis products. These biocompounds are promising sources of plant-protecting tools and could be used as bio-weapons against pests, for example reducing the attractiveness of plants to different insects or reducing fungal growth development [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%